2018
DOI: 10.1155/2018/6814393
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Necroptosis-Dependent Signaling Pathway in Cerebral Ischemic Disease

Abstract: Necroptosis is the best-described form of regulated necrosis at present, which is widely recognized as a component of caspase-independent cell death mediated by the concerted action of receptor-interacting protein kinase 1 (RIPK1) and receptor-interacting protein kinase 3 (RIPK3). Mixed-lineage kinase domain-like (MLKL) was phosphorylated by RIPK3 at the threonine 357 and serine 358 residues and then formed tetramers and translocated onto the plasma membrane, which destabilizes plasma membrane integrity leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Recent findings implicated that NLRP3 inflammasome activation was originally participated in the process of brain damage caused by neuroinflammation in ischemic stroke. 24,25 Pringle et al 26 reported that IL-1β strongly potentiated hypoxia-induced neuronal damage. Consistent with these findings, we found that NLRP3 inflammasome was markedly activated as evidenced by the cleavage of caspase-1 and IL-1β in OGD/R microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings implicated that NLRP3 inflammasome activation was originally participated in the process of brain damage caused by neuroinflammation in ischemic stroke. 24,25 Pringle et al 26 reported that IL-1β strongly potentiated hypoxia-induced neuronal damage. Consistent with these findings, we found that NLRP3 inflammasome was markedly activated as evidenced by the cleavage of caspase-1 and IL-1β in OGD/R microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…During cerebral ischemia, neuronal pyroptosis and necroptosis are extensively affected (Xu et al, 2018;Dong et al, 2018). Pyroptosis is thought to be executed by receptorinteracting protein kinase 3 (RIPK3) and a pseudokinase, mixed lineage kinase domain-like protein (MLKL).…”
Section: Ferroptosis and Pyroptosis And Necroptosismentioning
confidence: 99%
“…The expression of both RIP3 and MLKL demonstrates a significant increase in atherosclerotic plaques compared to normal arteries ( Karunakaran et al, 2016 ). Besides, numerous studies have shown that MLKL-dependent necroptosis is critical in the pathogenesis of brain diseases, especially ischemic brain injury and neurodegenerative diseases ( Zhang et al, 2017 ; Xu et al, 2018a ). Necroptosis has also been implicated in acute kidney injury (AKI) and chronic renal disease ( Imamura et al, 2018 ).…”
Section: Mlkl-dependent Necrosis—necroptosismentioning
confidence: 99%